Irrigation scheduling on wheat for maximum yield in the cerrado region - Guerra, Antonio Fernando (Pesquisa Agropecuaria Brasileira, 1995)
The response of wheat (Triticum aestivum L.) to six levels of soil-water tension was studied under field conditions in a Dark-Red Latossol of the Brazilian Savannah Region. The crop was irrigated when the soil-water tension measured with tensiometers or gypsum blocks reached values of 41, 51, 69, 185, 562 and 993 kPa at a depth of 10 cm throughout the crop cycle. The water was applied to the crop by using a plastic hose connected to a PVC perforated tube to assure uniform water distribution on the experimental plots. The results indicate a reduction in grain yield with the increase in soil-water tension. The highest yield (6,952 kg/ha) was obtained with the lowest soil-water tension (41 kPa). The yield components that caused reduction in yield were the number of spikes per square meter, number of spikelets per spike and number of grains per spike. No significant difference was observed for 1,000-grain weight and hectoliter-grain weight. The results indicate that plants define their development and yield as a function of soil-water tension to maintain grain quality.